2023
DOI: 10.3389/fimmu.2023.1052756
|View full text |Cite
|
Sign up to set email alerts
|

Role of the inflammasome in insulin resistance and type 2 diabetes mellitus

Abstract: The inflammasome is a protein complex composed of a variety of proteins in cells and which participates in the innate immune response of the body. It can be activated by upstream signal regulation and plays an important role in pyroptosis, apoptosis, inflammation, tumor regulation, etc. In recent years, the number of metabolic syndrome patients with insulin resistance (IR) has increased year by year, and the inflammasome is closely related to the occurrence and development of metabolic diseases. The inflammaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 215 publications
2
22
0
Order By: Relevance
“…The exposure to smoke has been discovered to stimulate the activation of inflammasomes and the accumulation of free radicals in both the circulatory system and local keratinocytes of the skin 38–41 . Both the activation of inflammasome as well as the accumulation of ROS have been firmly established as crucial factors in the development of vitiligo and diabetes 42,43 . In our study, we observed no distinct benefit for vitiligo development, which is more in line with our expectations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The exposure to smoke has been discovered to stimulate the activation of inflammasomes and the accumulation of free radicals in both the circulatory system and local keratinocytes of the skin 38–41 . Both the activation of inflammasome as well as the accumulation of ROS have been firmly established as crucial factors in the development of vitiligo and diabetes 42,43 . In our study, we observed no distinct benefit for vitiligo development, which is more in line with our expectations.…”
Section: Discussionsupporting
confidence: 91%
“…[38][39][40][41] Both the activation of inflammasome as well as the accumulation of ROS have been firmly established as crucial factors in the development of vitiligo and diabetes. 42,43 In our study, we observed no distinct benefit for vitiligo development, which is more in line with our expectations. Considering the harm to DM occurrence caused by smoking, especially the additive effect of smoking and disease severity, we strongly recommend that patients with vitiligo should quit smoking.…”
Section: Methodssupporting
confidence: 92%
“…36 Hyperglycemia also causes deregulation of NLRP1,3,6, NLRC4, and AIM2 and is associated with insulin resistance and development of diabetic complications. 37 There is considerable evidence that both of the diseases are epigenetically altered, resulting in the upregulation of inflammasome components. 38 This study analyzed the association of periodontitis and diabetes with salivary levels of AIM2, IFI16, and the potential confounders that could mediate the observed relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental requirement for AIM2 inflammasome activation is the presence of cell free DNA (cfDNA). 37 These are small DNA fragments present in plasma, serum, urine, and other fluids in our body, inclusive of saliva. 43 cfDNA is derived from cell necrosis, apoptosis, and autonomic release following cellular synthesis of nucleic acids and represents nuclear as well as mitochondrial DNA (mtDNA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation